Effects of autologous platelet-rich plasma on implantation and pregnancy in repeated implantation failure: A pilot study - Nazari, Leila (Int J Reprod Biomed, 2016)
BACKGROUND: Repeated implantation failure (RIF) is a major challenge in reproductive medicine and despite several methods that have been described for management, there is little consensus on the most effective one. OBJECTIVE: This study was conducted to evaluate the effectiveness of platelet-rich plasma in improvement of pregnancy rate in RIF patients. MATERIALS AND METHODS: Twenty women with a history of RIF who were candidates for frozen-thawed embryo transfer were recruited in this study. Intrauterine infusion of 0.5 ml of platelet-rich plasma that contained platelet 4-5 times more than peripheral blood sample was performed 48 hrs before blastocyst transfer. RESULTS: Eighteen participants were pregnant with one early miscarriage and one molar pregnancy. Sixteen clinical pregnancies were recorded and their pregnancies are ongoing. CONCLUSION: According to this study, it seems that platelet-rich plasma is effective in improvement of pregnancy outcome in RIF patients.